Patients' experiences with a behaviour change intervention to enhance physical activity in primary care: A mixed methods study - Westland, Heleen; Sluiter, Jill; Te Dorsthorst, Sophie; Schröder, Carin D; Trappenburg, Jaap C A; Vervoort, Sigrid C J M; Schuurmans, Marieke J (Public Library of Science, 2019)
Objective :To explore the experiences of patients at risk for cardiovascular disease in primary care with the Activate intervention in relation to their success in increasing their physical activity. Methods: A convergent mixed methods study was conducted, parallel to a cluster-randomised controlled trial in primary care, using a questionnaire and semi-structured interviews. Questionnaires from 67 patients were analysed, and semi-structured interviews of 22 patients were thematically analysed. Experiences of patients who had objectively increased their physical activity (responders) were compared to those who had not (non-responders). Objective success was analysed in relation to self-perceived success. Results: The questionnaire and interview data corresponded, and no substantial differences among responders and non-responders emerged. Participating in the intervention increased patients' awareness of their physical activity and their physical activity level. Key components of the intervention were the subsequent support of nurses with whom patients' have a trustful relationship and the use of self-monitoring tools. Patients highly valued jointly setting goals, planning actions, receiving feedback and review on their goal attainment and jointly solving problems. Nurses' support, the use of self-monitoring tools, and involving others incentivised patients to increase their physical activity. Internal circumstances and external circumstances challenged patients' engagement in increasing and maintaining their physical activity. Conclusion: Patients experienced the Activate intervention as valuable to increase and maintain their physical activity, irrespective of their objective change in physical activity. The findings enable the understanding of the effectiveness of the intervention and implementation in primary care.
Keywords: General Biochemistry,Genetics and Molecular Biology; General Agricultural and Biological Sciences; General; Journal Article